Penggunaan Model Pembelajaran Think Pair Share untuk Meningkatkan Kemampuan Berkomunikasi Siswa - Nurkhasanah, Siti (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2023)
This paper is a best learning practice, whereby using the Think Pare and Share (TPS) learning model can improve the communication skills of class IX.2 students of SMP Negeri 1 Gangga, North Lombok Regency, in the 2022/2023 academic year. The type of research used is pre-experimental with a one-shot case study design. The population and sample of this study were students of class IX.2 at SMP Negeri 1 Gangga. The research instrument used was a questionnaire. The activity took place in two meetings where the first meeting was a think and pair activity and the second meeting was a share activity. Students' communication skills, especially in presentation activities, are on average still low, from lack of confidence, unclear articulation, use of Indonesian to mastery of the material. Through the use of the Think Pare and Share (TPS) learning model, the results obtained are; 92.8% of students opened presentations with greetings, using good and correct Indonesian, 57.2%. Articulation or pronunciation that is clear and loud 82.1%. the ability to cooperate with friends 82.1%. An open attitude to questions from other participants is 21.%. Confidence 42.8% Students who have not mastered the material during presentations are quite high, although not half that is 46.5%, 53.5% feel doubtful between being excited and happy in presentations or not as much as 57.2% students feel capable interact with friends or other participants and students dress neatly during presentations, which is 89.2%.